A privileged ER compartment for posttranslational heteromeric assembly of an ion channel - Sudharsan Kannan; William Kasberg; Liliana R. Ernandez; Anjon Audhya; Gail A. Robertson (Proceedings of the National Academy of Sciences, 2025)
Mechanisms underlying heterotypic subunit assembly of ion channels and other oligomeric complexes are poorly understood. In the human heart, heteromeric assembly of two isoforms encoded by the human ether-à-go-go related gene ( hERG ) is essential for the normal function of cardiac I Kr in ventricular repolarization, with loss of hERG1b contributing to arrhythmias associated with long QT-syndrome (LQTS). While hERG1a homomers traffic efficiently to the plasma membrane, hERG1b homomers are retained in the endoplasmic reticulum (ER). When expressed together, the two subunits avidly associate during biogenesis. Seeking rules specifying heteromeric association, we characterized the fate of hERG1b proteins using confocal and superresolution imaging in fixed and live HeLa cells. We found hERG1b sequestered in punctate intracellular structures when expressed alone in HeLa cells. These puncta, which depend on the presence of an N-terminal “RXR” ER retention signal, represent a privileged ER subcompartment distinct from that containing ER-retained, type 2 (hERG-based) LQTS mutant proteins, which were rapidly degraded by the proteasome. Introducing hERG1a to cells with preformed hERG1b puncta dissolved these puncta by rescuing extant hERG1b. Rescue occurred by association of fully translated hERG1b with 1a, a surprising finding given previous studies demonstrating cotranslational heteromeric association. We propose that sequestration limits potentially deleterious surface expression of hERG1b homomeric channels while preserving hERG1b for an alternative mode of heteromeric hERG1a/1b channel assembly posttranslationally. These findings reveal a surprising versatility of biosynthetic pathways promoting heteromeric assembly.